Media barometer 2004 - Nordicom - Nordic Information Centre for Media and Communication Research, University of Gothenburg (University of Gothenburg, 2006)
The first Media Barometer was conducted in 1979 and since then the survey has been carried out annually. The purpose is to explore how the Swedish population is using different media during an average day.

Purpose:

Describe the trends and changes in people's use of mass media.

Mediebarometern genomfördes första gången 1979 och har sedan dess genomförts varje år. Undersökningen avser att belysa hur stor andel av den svenska befolkningen som en genomsnittlig dag tagit del av ett antal enskilda medier. Syftet är att beskriva tendenser och förändringar i människors utnyttjande av massmedier.

Syfte:

Beskriva tendenser och förändringar i människors nyttjande av massmedier.
Mediebarometern 2004
Keywords: mass media; massmedia; mass media exposure; massmediaexponering; newspaper readership; tidnings läsekrets; listening to music; musiklyssnande; book use; bokanvändning; local broadcasting; lokalsändningar; radio stations; radiostationer; satellite television; satellit-tv; television channels; tv-kanaler; cable television; kabel-tv; television news; tv-nyheter; internet; internet; internet access; internetåtkomst; electronic mail; elektronisk post; audio and video equipment; ljud- och videoutrustning; information retrieval; informationssökning; teletext; text-tv; mobile communication; mobilkommunikation; access to information and communications technology; tillgång till informations- och kommunikationsteknologi; households; hushåll; reading (activity); läsande; Media; Media; Information society; Informationssamhället; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap